A comprehensive analysis of the pyrolysis effects on oil shale pore structures at multiscale using different measurement methods. (15th July 2021) - Lei, Jian; Pan, Baozhi; Guo, Yuhang; Fan, YuFei; Xue, Linfu; Deng, Sunhua; Zhang, Lihua; Ruhan, A.
Abstract: It is useful in the clarifications of pore spaces at different scales in reservoir evaluations, and also helpful to exploit shale oil resources. The analysis of pores and fractures can be used to evaluate the reconstruction effects of pyrolysis in reservoirs. The existing analysis methods mainly adopt single scale data to study pores of certain sizes, which does not fully reflect the pore structures of oil shale. In this study, experiments regarding gas adsorption, SEM, MICP, NMR, and CT were conducted for the purpose of evaluating the effects of pyrolysis on the oil shale from the Wangqing. It was proposed to divide the pore spaces (0.1–10 6 nm) into seven levels for comparison purposes according to the order of magnitude, and then to evaluate the applicability of each method. The pyrolysis was observed to have caused the porosity of oil shale to markedly increase, and the sizes of the pores were found to change from mainly nano to co-developed micro-nano pores. The results indicated that a single pore detection method has its limitations since it is difficult to obtain multi-scale pore information. In order to understand the pore structures of oil shale, it is necessary to integrate multiple methods. Highlights: The pore structure of multi-scale oil shale is analyzed comprehensively. The influence of pyrolysis on the pore structure of oil shale was evaluated. The application effect of different measurement methods to oil shale is compared.